Qualidade da carne de frangos acometidos pela miopatia White Striping (WS) armazenados sob refrigeração e congelamento - Costa Filho, Djalma Vitorino (2022)
The objectives of this study were to understand to what extent the quality of severe WS chicken breast fillets is affected by storage under refrigeration and freezing conditions, in relation to physicochemical, sensory and aromatic parameters, together with the oxidative damage of lipid and protein. Chicken breasts were selected according to the visual appearance of the Pectoralis major muscle in severe WS (with white streaks greater than 1mm thick) and N (without white streaks on the surface). Then, the breasts were sectioned into fillets and stored under refrigeration conditions (±1 °C) for up to 14 days and freezing (± -18 °C) for up to 90 days. WS fillets have higher lipid content. WS and N fillets showed a drop in pH during refrigeration. The shear force (SF) did not differ between the WS and N samples; however, there was a significant reduction in the SF value at 11 and 14 days of storage under refrigeration, and at 45 and 90 days under freezing conditions. Regarding oxidative damage, a reduction in malondialdehyde (MDA) and carbonyl levels was observed, in addition to the interaction of these compounds with other compounds in raw, roasted and reheated fillets under refrigerated storage (14 days). The freezing condition significantly reduced the pH, SF and yellow intensity (b*) of the WS and N fillets without changing the moisture content, keeping the oxidative levels of the WS fillets in an MDA range that leads to the formation of flavors and unpleasant odors, which can be perceived by consumers. The higher content of carbonyls in the WS fillets in relation to the N fillets has a negative impact on the quality of the product (loss of essential amino acids) and on its digestibility. The number and concentration of volatile compounds, throughout the storage period, refrigerated and frozen, were higher in raw WS fillets compared to N fillets, even though there was a reduction at the end of the storage period. The volatile compounds with the greatest contribution were aldehydes, regardless of the type of fillet analyzed and storage condition. The volatile profile of the roasted N and WS meats was superior to that of the raw fillets at 0 days of storage, showing a significant reduction after 11 days in refrigeration, with no change when subjected to freezing for 90 days. A positive and conservative effect was observed on volatiles in WS breast when stored under freezing, different from that observed with N meat, which had a decrease in the volatile profile. During refrigerated and frozen storage, the sensory evaluator perceived a more intense characteristic odor of fresh chicken for the N and WS fillets, when evaluated raw or roasted, although a reduction in the odor of fresh chicken from the raw WS breast was observed at 11 days of refrigeration and 90 days of freezing. Therefore, it is recommended that the meats be stored under refrigeration and consumed within a period of up to 11 days so that the properties of the meats are maintained for consumption.